Effectiveness Analysis of Students’ Creative Thinking Skills Program by Optimizing The Development of Adobe Animate-Based Vlab Static Electricity Media - Indah Asmarany, Anugriaty; Mudriadi , Windi; Markiano Solissa , Everhard; Sudadi, Sudadi; Sudyana , I Nyoman (Mudir : Jurnal Manajemen Pendidikan, 2023)
This investigation created VLAB static electricity media using Adobe Animate to assess its practicability and gauge students' reactions to it. The study falls under the category of research and development (R&D), following the Borg & Gall development model, which is restricted to the main product revision stage. The evaluation tools are formulated based on student standards in simple language. The experiment was carried out on students in a classroom setting. Data gathering was done through interviews and surveys. The findings indicated that the Adobe Animate-based VLAB Static Electricity media was suitable for use as a learning tool based on the validation evaluation of material and media experts, with very feasible criteria. Limited development trials yielded positive student feedback with a good rating and creative thinking skills, resulting in a growing development category.